👤

1) 4x-3(3x-5)=6x+4
2)8-(4x-12)=8x-(3x-2)
3) 5(x-2)+(3+x)=6x-7
4) 4(3x-2)+5=2(6x-4)+x
5)x+1/4 =2x-4/5
6)3x-2/4=4x-5/3​


Odpowiedź :

Odpowiedź:

1) 4x-3(3x-5)=6x+4

4x -9x+15=6x+4

-5x+15 = 6x+4

-5x-6x=4-15

-11x=-11

x=1

2)8-(4x-12)=8x-(3x-2)

8-4x+12=8x-3x+2

20-4x=5x+2

-4x-5x=2-20

-9x=-18

x=2

3) 5(x-2)+(3+x)=6x-7

5x-10+3+x=6x-7

6x-7=6x-7

0=0, L=P ----> równanie tożsamościowe

4) 4(3x-2)+5=2(6x-4)+x

12x-8+5=12x-8+x

x=5

5) x+1/4 =2x-4/5

x-2x=-4/5 - 1/4

-x= -21/20

x= 1 1/20

6) 3x-2/4=4x-5/3​

3x-1/2=4x-5/3

3x-4x= -5/3+1/2

-x= -7/6

x=7/6

Go Studier: Inne Pytanie